Structural steel plate damage detection using non destructive testing, frame energy based statistical features and artificial neural networks - Paulraj, Murugesa Pandiyan, Dr.; Sazali, Yaacob, Prof. Dr.; Mohd Shukry, Abdul Majid; Mohd Nor Fakhzan, Mohd Kazim; Pranesh, Krishnan (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis.